nalisis Penerapan Model Pembelajaran Problem Based Learning (PBL) Pada Materi Ekosistem di Kelas X SMA PAB 4 Sampali` - Annisa Ridha Riyani; Cindi Santika Ramadina; Geovany Panjaitan; Maylani Magdalena Malau; Widya Arwita, Rizal Mukra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model on ecosystem material in class X of SMA PAB 4 Sampali, as well as to examine students’ responses and the obstacles encountered. This research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results show that the implementation of PBL followed its learning syntax and was able to increase students’ activeness, participation, and critical thinking skills. Learning became more contextual and meaningful as it was based on real-life problems. The obstacles encountered were related to students’ understanding of tasks and their ability to construct answers, but these could be addressed through teacher guidance. Therefore, the PBL model is effective in improving the quality of learning on ecosystem material.